Health status perception and airflow obstruction in five Latin American cities: the PLATINO study - Montes de Oca, Maria (2009)
Background: COPD is a highly prevalent disease but underdiagnosed, undertreated and possibly under-recognized by patients. Limited information exists regarding patients' perception of COPD severity. We compared patients' general, health status perception, degree of breathlessness and physical activity limitation with the severity of their respiratory condition measured by airway obstruction, in a population-based sample.Methods: We used postbronchodilator FEV(1)/FVC < 0.70 to define COPD. Patients' perception of their general. health status was derived from the question in general, you would say that your health is: excellent, very good, good, fair or poor?Results: Spirometry was performed in 5314 subjects: an FEV(1)/FVC ratio below 0.70 was found in 759 subjects. in persons with COPD, general. health status decreased with increasing GOLD stages. Over one-half of subjects with stage 2 and one third of those with stages 3 and 4 reported their health status as good to excellent. There was also a disparity between airway obstruction severity and breathlessness intensity. Although the more severe COPD stages were frequently associated with significant compromise of work and everyday activities, patients often tended to provide an optimistic self evaluation of their health status.Conclusions: the discrepancy observed between general health status, dyspnea severity, physical activity limitation and airway obstruction most likely reflect patients' underperception of disease severity, emphasizing the need for improving case-finding measures and multi-component evaluation of COPD subjects. (C) 2009 Elsevier B.V. All rights reserved.